1994
DOI: 10.1111/j.1540-8167.1994.tb01122.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Observations in the Myocardium Beyond the Region of Acute Coagulation Necrosis Following Radiofrequency Catheter Ablation

Abstract: RF catheter ablation results in ultrastructural damage to the myocardium extending up to 6 mm beyond the acute pathologic RF lesion border as defined by NBT histochemical staining.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 12 publications
1
48
1
Order By: Relevance
“…RFA causes tumor destruction (necrosis) by thermal coagulation and protein denaturation as a consequence of frictional heating converting electromagnetic waves in a heat source by ionic agitation [33,34] through a percutaneously ultrasoundguided fine electrode needle inserted in the hepatic nodule [35]. Although mitochondrial destruction has been described as early and specific effect of RFA [36] together with an extension of damages outside the region of necrosis [37], little is known, on the effects of this procedure on hepatic function and finally on its general safety. This study investigated these points specifically in vivo by the use of breath test analysis and demonstrated for the first time that RFA and TACE treatments differently affect specific hepatic metabolic functions.…”
Section: Discussionmentioning
confidence: 99%
“…RFA causes tumor destruction (necrosis) by thermal coagulation and protein denaturation as a consequence of frictional heating converting electromagnetic waves in a heat source by ionic agitation [33,34] through a percutaneously ultrasoundguided fine electrode needle inserted in the hepatic nodule [35]. Although mitochondrial destruction has been described as early and specific effect of RFA [36] together with an extension of damages outside the region of necrosis [37], little is known, on the effects of this procedure on hepatic function and finally on its general safety. This study investigated these points specifically in vivo by the use of breath test analysis and demonstrated for the first time that RFA and TACE treatments differently affect specific hepatic metabolic functions.…”
Section: Discussionmentioning
confidence: 99%
“…Especially in early stages after cell injury, alterations are too discrete to be detected by light microscopy. Transmission electron microscopy is feasible for detecting ultrastructural changes [23]. However, this method is laborious and expensive and thus hardly suitable for analyzing specimens of the required size.…”
Section: Discussionmentioning
confidence: 99%
“…A correlation between hyperthermal enzyme damage and cell killing is known for several enzymes [27,28]. Viability staining with TTC has been successfully used in different tissues to detect early changes after heat-related and ischemic damage and is known to be directly related to ultrastructural defects that are visible by electron microscopy [23,[29][30][31]. The mismatch between H & E and EM/viability staining is, among others, a matter of time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the number of thromboembolic complications of RFA is low, identification of the risk factors is difficult and the significance of the pathophysiological mechanisms of hemostasis activation during RFA has not been definitively established in studies published to date. T0 before insertion of sheaths, T1 end of EPS, T2 30 min after completion of RFA, DD D-dimers, TAT thrombin-antithrombin III, PAI-1 plasminogen activator inhibitor type 1, t-PA tissue-type plasminogen activator, CPAi circulating platelet aggregates index, LCL lower confidence level, UCL upper confidence level Potential mechanisms of thrombogenesis during ablation procedures are multiple and include endothelial disruption, coagulation necrosis, electroporation injury, mechanical damage of the vessel wall, and heating of circulating blood elements by RF energy [9][10][11][12][13][14][15][16][17][18]. Sasano et al [19] concluded that the thrombogenesis caused by RFA has 2 phases; in the acute phase hemostasis activation occurs during placement of the catheters and in the delayed phase thrombogenesis is the result of endothelial damage caused by the RF current.…”
Section: Discussionmentioning
confidence: 99%